Solve for y -6*(-2y)=12

Math
-6⋅(-2y)=12
Multiply -2 by -6.
12⋅y=12
Divide each term by 12 and simplify.
Tap for more steps…
Divide each term in 12⋅y=12 by 12.
12⋅y12=1212
Cancel the common factor of 12.
Tap for more steps…
Cancel the common factor.
12⋅y12=1212
Divide y by 1.
y=1212
y=1212
Divide 12 by 12.
y=1
y=1
Solve for y -6*(-2y)=12

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top